A Form of Independent Curriculum, an Overview of Independent Learning at State Elementary School 05 Gelumbang Muaraenim - Mustafiyanti, Mustafiyanti; Putri , Mesi Pramesia; Muyassaroh, Muyassaroh; Noviani, Dwi; Dylan, Moatti (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. The Merdeka Curriculum as an alternative curriculum overcomes learning setbacks during the pandemic which gives